Vidas e corpos em trânsito: tráfico de travestis e transexuais brasileiras com a finalidade de exploração sexual no contexto da crise do capital - Navas, Kleber de Mascarenhas (2016)
This thesis is to study the subject of trafficking in Brazilian transvestites and transsexuals for the purpose of sexual exploitation. The overall objective is to analyze and critically understand the determinations of human trafficking for the purpose of sexual exploitation of transvestites and transsexuals in the transnational sex trade, as well as ways of coping in terms of public policy. In this sense, we analyze the movement of transvestites and transsexuals in sex markets towards southern European countries, as well as the dynamics of these displacements approaches the fraud notions, coercion or abuse of vulnerability that characterize human trafficking in order to detect crime evidence about this phenomenon. From a theoretical point of view, it is part of Dialectical Materialism history as a foundation. The methodological procedures were quantitative and qualitative approach, with field research conducted with semi-structured script interview and applied with two subject. The main results of the research show that the subject surveyed were victims of human trafficking and that in such cases, there are specific compared with those involving women and adolescents, the main victims of this phenomenon. We observed also that the faces of human trafficking in the contemporary world is reactualized and it is necessary to analyze the crisis of capital of the context in which it appears, as it influences both the dynamics of trafficking, as the confrontation policies, which are presented, most of the time, with a camouflaged speech and hiding the true character of antimigration policies